2016
DOI: 10.1037/xlm0000174
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive memory: Animacy enhances free recall but impairs cued recall.

Abstract: Recent research suggests that human memory systems evolved to remember animate things better than inanimate things. In the present experiments, we examined whether these effects occur for both free recall and cued recall. In Experiment 1, we directly compared the effect of animacy on free recall and cued recall. Participants studied lists of objects and lists of animals for free-recall tests, and studied sets of animal-animal pairs and object-object pairs for cued-recall tests. In Experiment 2, we compared par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
100
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(129 citation statements)
references
References 71 publications
15
100
2
Order By: Relevance
“…Half of the participants studied the words under full attention and half under divided attention. Popp and Serra (2016) found that memory performance in a cued recall task was impaired when animate items were included in the word pairs, and suggested that animacy might capture the attention of participants, which would lead to the typical animacy effect that has been found in the literature. Further, Bonin et al (2015) found that the animacy effect persisted through a memory load exercise and suggested that there might be an attentional component related to the animacy effect such that animate items capture more attention than inanimate items.…”
Section: Animacy and Threatmentioning
confidence: 84%
See 4 more Smart Citations
“…Half of the participants studied the words under full attention and half under divided attention. Popp and Serra (2016) found that memory performance in a cued recall task was impaired when animate items were included in the word pairs, and suggested that animacy might capture the attention of participants, which would lead to the typical animacy effect that has been found in the literature. Further, Bonin et al (2015) found that the animacy effect persisted through a memory load exercise and suggested that there might be an attentional component related to the animacy effect such that animate items capture more attention than inanimate items.…”
Section: Animacy and Threatmentioning
confidence: 84%
“…The animacy effect has been replicated across a variety of experiments, including with recognition memory (Bonin, Gelin, & Bugaiska, 2014), independent of encoding instructions (Gelin, Bugaiska, Méot, & Bonin, 2017;Leding, 2018), for picture stimuli (Bonin et al, 2014), and with children participants (Aslan & John, 2016; see Nairne, VanArsdall, & Cogdill, 2017 for a review). Popp and Serra (2016) further explored the effect of animacy and created a normed list of animate and inanimate items where the two lists were equated on the characteristics of length, frequency, mental imagery, and concreteness. They found the animacy effect in free recall but found that cued recall was typically impaired when animate items were included in the pairs, except in a condition where Swahili words were paired with animate English words, similar to the results of VanArsdall, Nairne, Pandeirada, and Cogdill (2015).…”
Section: The Animacy Effectmentioning
confidence: 99%
See 3 more Smart Citations